RAFT Copolymerization of Styrene and Maleic Anhydride with Addition of Ascorbic Acid at Ambient Temperature - Juxiang Luo; Deshu Cheng; Mingchun Li; Meihua Xin; Weifu Sun; Wangchuan Xiao (Advances in Polymer Technology)
A novel method for RAFT copolymerization of styrene (St) and maleic anhydride (MAh) at ambient temperature using ascorbic acid (Asc) as an initiator is reported. Various experimental conditions including reaction component, monomer composition, the amount of Asc, and temperature were investigated in terms of monomer conversion, molecular weight, and molecular weight distribution. In this system, the copolymer of styrene/maleic anhydride (SMA) with well-regulated molecular weight and low molecular weight distribution (Mw/Mn=1.30) was obtained, and the conversion of monomer was 70.4% after 12 hours at 25°C. The NMR spectra demonstrated that the copolymer synthesized possesses a strictly alternating structure. Furthermore, the proposed mechanism adapted to the RAFT copolymerization of St and MAh initiated by Asc at ambient temperature is presented. Using this new methodology, it is possible to achieve well-defined SMA under mild conditions by RAFT copolymerization.